Optimization of conditions required for the characterization of Escherichia coli promoters responsive to inter-species interaction with commensal partners : Klebsiella pneumoniae and Enterococcus faecalis. - Kong, Kiat Whye. (2009)
A promoter-capture library (Lib39) was previously constructed in Escherichia coli based on the dual fluorescence system, which can distinguish E. coli from other species and monitor promoter activities. By using Lib39, a strategy was designed to determine the effect of Klebsiella pneumoniae and Enterococcus faecalis on E. coli promoter activities. This study aims to verify the feasibility of this strategy. FSC-M/SSC-M subpopulation of K. pneumonia and FSC-H and SSC-H subpopulations of E. faecalis are preferred after analyzing their recovery percentage. After sequencing 40 randomly picked library clones, Lib39 was found to have a good coverage of E. coli genome and promoters. FACSAriaTM was unable to detect the assumed red fluorescent (R+) percentage, which may be due to the limitation of FACSAriaTM in detecting R+ events. Culturing in various temperatures and incubation times were unable to increase the library’s R+ events. A clone, containing a constitutive promoter upstream of mAsRed2, showed an increase in red intensity after static incubation in various conditions, implying that mAsRed2 is functioning but requires longer time to mature. Presence of A-U rich region in the untranslated mRNA may be the reason for ineffective mAsRed2 expression in some of the promoter-mAsRed2 fusions due to RNase E degradation.